2018
DOI: 10.3390/ijerph15020290
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Stress and Suicidal Ideation in the Disclosure of Sexual Orientation among Young French LGB Adults

Abstract: Background: Lesbians, gays, and bisexual people (LGB) present high levels of suicidal ideation. The disclosure of sexual orientation is a stressful experience which presents a high suicide risk. Research has not paid sufficient attention to stress during this disclosure in order to understand suicide among LGB people. The aims of this study were to investigate: (1) the characteristics of stress during this revelation, more precisely cognitive appraisal, emotions, and coping; and (2) associations between these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…A study among young French LGB adults demonstrated how the disclosure of sexual orientation as a stressful experience (one domain of the “minority stress”) is related to elevated suicide risk [ 16 ]. They explored associations between characteristics of stress (emotions, cognitive appraisal, and coping) and suicidal ideation and concluded that avoidance strategies had a direct effect on suicidal ideation, and mediated the link between primary appraisal (risk “Harm myself and others”) and suicidal ideation.…”
Section: Peculiarities Of Vulnerable Groups For Suicidalitymentioning
confidence: 99%
“…A study among young French LGB adults demonstrated how the disclosure of sexual orientation as a stressful experience (one domain of the “minority stress”) is related to elevated suicide risk [ 16 ]. They explored associations between characteristics of stress (emotions, cognitive appraisal, and coping) and suicidal ideation and concluded that avoidance strategies had a direct effect on suicidal ideation, and mediated the link between primary appraisal (risk “Harm myself and others”) and suicidal ideation.…”
Section: Peculiarities Of Vulnerable Groups For Suicidalitymentioning
confidence: 99%
“…The category that emerged through the findings of various authors (Baams et al, 2015;Baiocco et al, 2014;Calvo, 2018;Castillo, 2010;Charbonnier et al, 2018;Granados-Cosme & Delgado-Sánchez, 2008;Lagazzi, 2016;Ortiz-Hernández, 2005;Ortiz-Hernández & García, 2005;Pineda-Roa, 2019;Pinto-Cortez et al, 2018) who identified in their participants, victims of homophobic aggressions (gays, lesbians, bisexuals, transsexuals, and transgender) the presence of mental disorders, such as anxiety or depression, also found behaviors oriented to self-harm, from the assimilation of all these prejudices around one's sexual orientation (Calvo, 2018). Other authors (Calvo, 2018;Ortiz-Hernández & García, 2005) focused on exploring participant´s social representations that revolved around their sexual orientation, even rejecting it and, showing homophobic behaviors, this process they called Internalized Homophobia, characterized by a dislike for one's self, feelings regarding that there was something wrong with them, that their feelings were unnatural; and even, that they should be punished (Lagazzi, 2016;Pinto-Cortez et al, 2018), they perceived themselves as a burden, or a disappointment to their loved ones (Charbonnier et al, 2018). A relevant finding was the relationship between internalized homophobia and suicidal ideation and attempt, as it implied the contradiction between "wanting to be" and "should be," which hindered the participants' experience of "coming out" (Baiocco et al, 2014;Charbonnier et al, 2018;Pineda-Roa, 2019), the feelings that emerged were fear, uncertainty, stress and anxiety of being rejected or stigmatized (Baams et al, 2015;Ortiz-Hernández, 2005).…”
mentioning
confidence: 99%
“…Other authors (Calvo, 2018;Ortiz-Hernández & García, 2005) focused on exploring participant´s social representations that revolved around their sexual orientation, even rejecting it and, showing homophobic behaviors, this process they called Internalized Homophobia, characterized by a dislike for one's self, feelings regarding that there was something wrong with them, that their feelings were unnatural; and even, that they should be punished (Lagazzi, 2016;Pinto-Cortez et al, 2018), they perceived themselves as a burden, or a disappointment to their loved ones (Charbonnier et al, 2018). A relevant finding was the relationship between internalized homophobia and suicidal ideation and attempt, as it implied the contradiction between "wanting to be" and "should be," which hindered the participants' experience of "coming out" (Baiocco et al, 2014;Charbonnier et al, 2018;Pineda-Roa, 2019), the feelings that emerged were fear, uncertainty, stress and anxiety of being rejected or stigmatized (Baams et al, 2015;Ortiz-Hernández, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation